Secondary chondrosarcoma in familial multiple enchondromatosis - García-Ramos, Hugo (2019)
We present the case of a 34-year-old male with chondrosarcoma secondary to familial multiple enchondromatosis, an autosomal dominant disease. Radiography and chest CT showed a dense mass with calcifications in the three anterior quarters of the upper left hemithorax. The pathological anatomy was compatible with a metastatic chondrosarcoma of primary degree of left rib cage.